Un'illusione di femminile semplicità Gli Annali delle Orsoline di Bellinzona (1730-1848) - Nicoli, Miriam (La memoria restituita, 2021)
This volume combines religious history and a gender perspective in order to study women's life trajectories as they balanced between adapting to the norm, taking initiative within the community, and managing conflicts and different conceptions of spirituality. In their extensive introductory essay, the authors focus on two main events, in particular, an internal revolt and an external revolution: the first within the convent, which saw two factions opposing each other, led by the founding mother and the founder's daughter, respectively; the second was epochal, leading to the end of the Old Regime in the territories of the old Helvetic Confederation. For the Ursulines, it prompted a fierce counter-revolution as they sought to restore their community life. The essay and the documents written by women and published in the book - in particular, the book of the Annali - shed light on the society of the time: compiled in a meticulous and rare chronicle, they allow us to enter into an Ursuline institute and to grasp its various facets, illustrating the variety and density of relationships and power games. Last but not least, they permit us to reflect on the literacy and agency of Catholic women in an Alpine region.